2023
DOI: 10.3390/pathogens12080993
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Herpesviruses in Sera and Saliva of Asymptomatic HIV-Infected Individuals Using Multiplex RT-PCR DNA Microarray

Irna Sufiawati,
Rahmi Harmiyati,
Nanan Nur’aeny
et al.

Abstract: Human herpesviruses (HHVs) are frequently linked to an increased risk of acquiring human immunodeficiency virus (HIV), and vice versa. This study aimed to detect human herpesvirus (HHV) members in the sera and saliva of asymptomatic HIV-infected individuals. Paired saliva and serum samples were obtained from 30 asymptomatic HIV-infected individuals. HHVs were detected with a multiplex reverse transcription-polymerase chain reaction (RT-PCR) DNA microarray Clart®Entherpex kit. A total of 30 subjects were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“… 11 However, a study has reported that men are more frequently affected than women. 17 Intrinsic biological differences between men and women can have a significant impact on the progression of HIV infection. These sex-related factors influence HIV acquisition, viral replication, pathogenesis, and the type of ART used for pre-exposure prophylaxis or treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 11 However, a study has reported that men are more frequently affected than women. 17 Intrinsic biological differences between men and women can have a significant impact on the progression of HIV infection. These sex-related factors influence HIV acquisition, viral replication, pathogenesis, and the type of ART used for pre-exposure prophylaxis or treatment.…”
Section: Discussionmentioning
confidence: 99%